Redo isolated tricuspid valve surgery: prediction of in-hospital mortality using the TRI-SCORE. (3rd October 2022) - Dreyfus, J; Bohbot, Y; Coisne, A; Lavie-Badie, Y; Riant, E; Modine, T; Le Tourneau, T; Tribouilloy, C; Donal, E; Habib, G; Selton-Suty, C; Iung, B; et al.
Abstract: Background: Redo isolated tricuspid valve surgery (ITVS) is rarely performed. The TRI-SCORE reliably predicts in-hospital mortality after ITVS on native valve but has not been tested in the setting of redo interventions. Purpose: We aimed to compare the predictive value of the TRI-SCORE to other surgical risk scores for redo ITVS. Methods: Using a mandatory administrative database, we identified all consecutive adult patients who underwent a redo ITVS at 12 French tertiary centers between 2007 and 2017. Baseline characteristics and outcomes were collected from chart review and the TRI-SCORE, Logistic EuroSCORE, EuroSCORE II and STS were calculated. Results: We identified 70 patients who underwent a redo ITVS (mean age 54±15 years, 63% female). Prior intervention was a repair in 51% and a replacement in 49%. A tricuspid valve replacement was performed in all patients. In-hospital mortality was 10%. The TRI-SCORE was the only risk score associated with in-hospital mortality (p=0.01). Area under the receiver operating characteristic curve for the TRI-SCORE was 0.83, much higher than with logistic EuroSCORE (0.58), EuroSCORE II (0.61) or STS (0.59). The table presents the observed and predicted values of in-hospital mortality according to TRI-SCORE categories. Conclusion: The TRI-SCORE accurately predicted in-hospital mortality after redo isolated tricuspid valve surgery and may guide the clinical decision-making process especially as transcatheter therapies are emerging. Funding Acknowledgement: Type of funding sources: None.